Significance And Classification of Mineral Fertilizers (Texas Journal of Engineering and Technology, 2022)
There is a strong raw material base in our country, which is able to entirely providing the demands of economy in mineral resources. The large reserves of raw materials allowed operating the leading enterprises of the chemical industry such as Almalyk “Ammofos-Maxam” JSC, “MaxamChirchik” JSC, “Ferganaazot” JSC, “Navoiyazot” JSC, “Tashkent Paint Factory” JV, Dehkanabad potassium fertilizers plant” UE, “Kungrad soda plant” UE, “Shurtan gas chemical complex” LLC, “Kungrad sodium sulfate” JV and a number of other chemical enterprises. Currently, large chemical enterprises operate in Almalyk, Chirchik, Fergana, Kokand, Navoi, Shurtan, Dehkanabad and other regions of the country. Agricultural crops area cover about 13% of the Earth surface. It is impossible to expand the area under crops. Nevertheless, the population of our planet is constantly growing, and it is necessary to further increase productivity to provide them with food. One of the most important ways of this is using mineral fertilizers. Fertilizer is a substance designed to improve plant nutrition and increase soil fertility.